Investigating the performance of sewage treatment plants of IIUM Gombak campus - Nuruzzaman, Md.; Al-Mamun, Abdullah; Salleh, Md. Noor (2015)
The effluent quality of the Sewage Treatment Plants (STPs) located at International Islamic University Malaysia (IIUM) Gombak campus has been investigated in this paper. The main objective of this paper is to investigate whether the STPs are fulfilling the allowable effluent quality or not. Effluent quality data was collected from the STP operators of IIUM. The effluent quality has been checked against the Malaysian standard of STP effluent. It has been found that Ammoniacal Nitrogen (AN) concentration in the effluent is frequently higher than the allowable limit of 20 mg/L. Biochemical Oxygen Demand (BOD) concentration is below the Standard B limit but exceeding the limit of Standard A. However, the Total Suspended Solids (TSS) concentration is satisfactory as it is lower than the acceptable limit of 100 mg/L. After reviewing several AN removal methods, it has been suggested to upgrade extended aeration component in the STPs.